Perancangan dan Implementasi Api Pada Aplikasi Deteksi Mata Katarak Menggunakan Google Cloud Run - Muh Hafizin; Paniran Paniran (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Cataracts are the leading cause of blindness in Indonesia, with a prevalence of 1.5%. Unfortunately, many people overlook regular eye examinations that are crucial for early detection. As age increases, eyes become more susceptible to conditions like cataracts, characterized by clouding of the eye's lens. Addressing this challenge, Google Cloud Run has been implemented to develop a fast, efficient, and scalable cataract detection API. This initiative aims to facilitate easier access for healthcare professionals and the general public. The application is expected to enhance early screening, early detection, and prevention of serious eye conditions such as cataracts, ultimately improving quality of life through more effective prevention and treatment efforts.